The demands on nursing curriculum flexibility towards the need of global workforce: A systematic review - Hardy, Syaifoel; Hadi, Noor; Tukayo, Isak Jurun Hans (Journal of Holistic Nursing Science, 2021)
The demand for Indonesian nurses to work abroad has increased over the last five years. The challenge is that the orientation of the nursing education curriculum in Indonesia is still local, not yet leading to international standards. As a result, only a small number of nurses passed the selection, the process is longer, and the recruitment cost is higher. Therefore, this review aims to identify the global need for Indonesian nurses and provide an overview of the importance of structured planning in terms of nursing education curriculum related to job opportunities overseas. The study grouped, allocated, organized, and used relevant library variations. Researchers conducted a literature study regarding the demand for Indonesian nurses, the development of education and curriculum from several sources such as the Ministry of Health, the Indonesian Migrant Workers and Protection Agency (BP2MI), the Ministry of Higher Education, World Health Organization (WHO), as well as the latest journals, from 2016 to 2021. The data were reviewed, analyzed and alternative solutions were identified. The analytical review shows the demands on Indonesian nurses keep on growing. The magnitude of this demand is an opportunity as well as challenges that need to be anticipated earlier in terms of the nursing education curriculum and the Government policymakers. Keywords: nursing education; global need of nursing; clinical practice; health policy maker